2018
DOI: 10.1155/2018/9742154
|View full text |Cite
|
Sign up to set email alerts
|

UVA Irradiation Enhances Brusatol‐Mediated Inhibition of Melanoma Growth by Downregulation of the Nrf2‐Mediated Antioxidant Response

Abstract: Brusatol (BR) is a potent inhibitor of Nrf2, a transcription factor that is highly expressed in cancer tissues and confers chemoresistance. UVA-generated reactive oxygen species (ROS) can damage both normal and cancer cells and may be of potential use in phototherapy. In order to provide an alternative method to treat the aggressive melanoma, we sought to investigate whether low-dose UVA with BR is more effective in eliminating melanoma cells than the respective single treatments. We found that BR combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…For instance, in A549 NSCLC cells resistant to radiation, Brusatol was found to dose-dependently decrease the NRF2 protein levels and to enhance the efficacy of ionizing radiations, by inducing ROS-dependent DNA damage and cell death [312]. Also, Brusatol was recently found to impair cell growth and proliferaton of human A375 melanoma cells both in vitro and in vivo (NOD/SCID xenografted mice) when used in combination with UVA treatment, leading to increased ROS generation and apoptosis due to AKT impairment [313]. Also, Karathedath et al, reported that NRF2 overexpression in AML cell lines and primary AML samples caused resistance to Cytarabine, Daunorubicin and Arsenic trioxide (ATO).…”
Section: Natural Compounds That Impair Nrf2 Signaling By Interferingmentioning
confidence: 99%
“…For instance, in A549 NSCLC cells resistant to radiation, Brusatol was found to dose-dependently decrease the NRF2 protein levels and to enhance the efficacy of ionizing radiations, by inducing ROS-dependent DNA damage and cell death [312]. Also, Brusatol was recently found to impair cell growth and proliferaton of human A375 melanoma cells both in vitro and in vivo (NOD/SCID xenografted mice) when used in combination with UVA treatment, leading to increased ROS generation and apoptosis due to AKT impairment [313]. Also, Karathedath et al, reported that NRF2 overexpression in AML cell lines and primary AML samples caused resistance to Cytarabine, Daunorubicin and Arsenic trioxide (ATO).…”
Section: Natural Compounds That Impair Nrf2 Signaling By Interferingmentioning
confidence: 99%
“…In another very recent study, the cotreatment with Brusatol and UVA led to the inhibition of A375 melanoma cell proliferation triggering ROS-dependent apoptosis. Furthermore, decreased NRF2 expression was shown to attenuate colony formation and tumor development from A375 cell xenograft in heterotopic murine models, supporting the notion that the combined use of Brusatol and UVA might offer a valuable therapeutic option against malignant melanoma through the disruption of the tumor antioxidant defenses [291] (see Table 1). Importantly, apart from the antitumor effects on solid tumors, the chemosensitizing properties of Brusatol were also recently confirmed in hematological malignancies by Karathedath and colleagues.…”
Section: Therapeutic Strategies For Nrf2 Inhibition In Cancermentioning
confidence: 80%
“…Elevated Nrf2 expression in melanoma is correlated with a deeper Breslow index (that describes how deeply the melanoma invades into the skin), invasive phenotype, nodular growth, and poor survival [ 38 ]. It was shown that co-treatment of brusatol, a potent Nrf2 inhibitor, and UVA, a ROS-inducer, suppressed melanoma cell proliferation in vitro and in vivo , and led to apoptosis [ 41 ].…”
Section: Balancing Oxidative Stress By Increasing Antioxidant Power Imentioning
confidence: 99%
“…Drug-resistant cells restore DFNA to promote lipid saturation and protect melanoma from ROS damage and lipid peroxidation. DNFA pathway inhibition, whether by targeting of SREBP1, or by inhibition of DNFA enzymes, exerts potent cytotoxic effects on both drug-naïve and drug-resistant melanoma cells [ 41 , 106 ]. These data indicate that targeting of SREBP-1 and DNFA may offer a new strategy to overcome BRAFi resistance.…”
Section: Metabolic Rewiring In Brafi-resistant Melanoma: the Role Ofmentioning
confidence: 99%